Determination the Index of Radioactive Risk In The Batang Kuantan River - Genesa Hatika, Rindi; Dewata, Indang; ., Alizar; Subekti, Purwo; Anwar, Saiful (International Journal of Engineering and Technology, 2018)
NORM is a material containing radioactive elements that exist naturally. All minerals and raw materials contain radionuclides from nature, most important for radiation protection purposes are the U-238, Th-232 and K-40 decay series. This element naturally grows and is considered a major contributor to the annual individual background radiation dose. Therefore, each individual can be exposed to NORM through various activities they do, one of which is gold mining activities. Gold mining in addition to causing exposure to NORM, is believed also can cause significant environmental damage. This study aims to determine the index of radioactive risks that resulted from gold mining activities in the batang kuantan river. The sample used for this research is soil from batang kuantan river which then analyzed using gamma ray spectrometry. The results show that the index of radioactive risk value indicated by all soil samples in the batang kuantan river is still below the predetermined maximum limit value.Â Â
Keywords: NORM; Soil; Gold Mine; Gamma Spectrometry